STRATEGI BAURAN PROMOSI ARMOR COFFEE - Shinta Hartini Putri Welly Herlina Sari (Universitas Informatika dan Bisnis Indonesia, 2018)
The development of cafes and restaurants in West Java, especially in Bandung is becoming very rapid development compared to other areas the increasing number of restaurants and cafes in Bandung, among others due to several things, including the business sector hospitality industry has a bright prospect , this field includes restaurant businesses, cafes, hotels and pubs that are still open because the demand for tourism services offered by Bandung is quite high. Like the emergence of Armor Coffee in 2015 located the park of Djuanda Dago Forest Park with a different atmosphere from other places, with a cool forest atmosphere that presents various types of coffee. Promotion is considered very important for the product of a marketer company known by the public, especially the target market of the company. In addition, promotion is also intended as an activity that can provide information and persuasion to consumers. The basic instrument that companies use to achieve marketing communications goals is called promotional mix or promotional mix. Keywords: promotional mix, Armor Coffee